Repeated inoculation of antimony resistant bacterium reduces antimony accumulation in rice plants. (June 2023) - Long, Jiumei; Zhou, Dongsheng; Wang, Jing; Huang, Binyan; Luo, Yuanlai; Zhang, Guocheng; Liu, Zui; Lei, Ming
Abstract: Applying beneficial bacteria in rice rhizosphere to manage heavy metal behaviour in soil-plant system is a promising strategy. However, colonization/domination of exogenous bacteria in rhizosphere soils remains a challenge. In this study, a bacterium Ochrobactrum anthropi, which showed the potential of transforming soluble Sb III into Sb2 O3 mineral, was repeatedly inoculated into the rice rhizosphere weekly throughout the rice growth period, and the colonization of this bacterium in rice rhizosphere soils and its effect on Sb accumulation in rice plants were investigated. Results showed that repeated inoculants changed the native bacterial community in rhizosphere soils in comparison with the control, but the inoculated O. anthropi was not identified as an abundant species. With weekly inoculation, the decrease in Sb in rice roots and straws was maintained throughout the rice growth period, with decrease percentages ranging from 36 to 49% and 33–35%. In addition, decrease percentages of Sb in husks and grains at the maturing stage obtained 34 and 37%, respectively. Furthermore, the XRD identified the formation of valentinite (Sb2 O3 ) on rice root in inoculation treatment, and the decrease percentages in aqueous Sb III in rhizosphere were 53–100% through the growth period. It demonstrated that weekly inoculants performed their temporary activity of valentinite formation, and reduced Sb accumulation in rice plants efficiently. This study suggests that regardless of successful colonization, repeated inoculation of beneficial bacteria is an option to facilitate the positive effects of inoculated bacteria in the management of heavy metal behaviour. Graphical abstract: Image 1 Highlights: Ochrobactrum anthropi did not dominate in rice rhizosphere with Weekly inoculation. Weekly inoculation of O. anthropi changed the native bacterial community. Weekly inoculation of O. anthropi maintained the decrease of Sb accumulation in rice plant. The decrease effect is related to the formation of mineral valentinite (Sb2 O3 ).